2008
DOI: 10.5688/aj720347
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based Learning Using the Online Medicare Part D Plan Finder Tool

Abstract: Objectives. To implement didactic and problem-based learning curricular innovations aimed at increasing students' knowledge of Medicare Part D, improving their ability to apply the online Medicare Prescription Drug Plan Finder tool to a patient case, and improving their attitudes toward patient advocacy for Medicare beneficiaries. Methods. A survey instrument and a case-based online Medicare Prescription Drug Plan Finder tool exercise were administered to a single group (n 5 120) of second-year pharmacy gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…18 Another study found that pharmacy students who learned about Part D in the classroom setting better understood the complexities of the benefit and empathized with beneficiaries regarding the challenges it poses. 19 In addition to assisting beneficiaries with the Part D benefit, pharmacists are ideally positioned to provide invaluable services in the area of MTM and vaccinations, including improved economic and health outcomes for patients through pharmacist-led MTM efforts.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another study found that pharmacy students who learned about Part D in the classroom setting better understood the complexities of the benefit and empathized with beneficiaries regarding the challenges it poses. 19 In addition to assisting beneficiaries with the Part D benefit, pharmacists are ideally positioned to provide invaluable services in the area of MTM and vaccinations, including improved economic and health outcomes for patients through pharmacist-led MTM efforts.…”
Section: Introductionmentioning
confidence: 99%
“…This will allow for targeted educational efforts to improve student selfefficacy, equipping students with the skills, confidence, and motivation needed to help Medicare beneficiaries in their communities after they graduate and become practicing pharmacists. Additionally, this program differs from many others 3,8,20 in that it combines coursework with community outreach and it is offered in partnership with the Alabama SHIP to increase its legitimacy. As seen in students' reflection comments, experiential education through community outreach helped prepare future pharmacists for real-world practice and increased their confidence and willingness to assist Medicare patients via realization of beneficiary cost-savings.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, and keeping in mind a possible floor effect from our evaluation scale, student confidence in knowledge and ability to provide services to Medicare beneficiaries increased after completion of the program. 3,20,26 Although students' pre-program knowledge was not assessed, self-reported changes in knowledge immediately post-program ensured that the experience remained timely and relevant. Future evaluation of student learning may focus on self-efficacy pre and post-program, utilizing a more nuanced scale to determine levels of change than used here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outreach curriculum, which has been described elsewhere, improves pharmacy student knowledge, skill mastery, and confidence in performing Part D outreach. 5 Early success with the program, coupled with interest from other schools of pharmacy in California, led to the development of a faculty training program with the goal of promoting broad-scale dissemination using a train-the-trainer approach. 5 Here we present evaluation data from our initial statewide faculty train-the-trainer program for the Part D community outreach component of the Partners in D program.…”
Section: Introductionmentioning
confidence: 99%